Biometabolic Distribution of Tc-3PRGD2 and its Potential Value in Monitoring Chemotherapeutic Effects - Jian-Guo Wu; Shao-Li Song; Xiang Zhou; Fan Wang; Yin-Yan Zhu; Lei Xie; Fan Zhang; Gang Huang (Molecular Imaging)
Previous studies have reported that 99m Tc-3PRGD2 is an excellent tumor imaging agent that showed a good correlation with integrin α v β 3 , a main factor of tumor-induced angiogenesis. In this study, we investigated the biometabolic distribution characteristics of 99m Tc-3PRGD2 with a continuous dynamic acquisition mode to explore the potential value of 99m Tc-3PRGD2 in monitoring chemotherapeutic effects in VX2 tumor models. Eighteen rabbits with 27 implanted VX2 squamous cell tumors were randomly divided into a nontreated control group (NTG, n = 8; 12 tumors) and a treatment group (TG, n = 10; 15 tumors). 99m Tc-3PRGD2 imaging was performed prior to cisplatin injection and repeated on days 0,1, 7, and 14 postinjection. Continuous dynamic scanning up to 30 minutes; static imaging at 0.5 hours, 1 hour, and 3 hours; and single-photon emission computed tomography/computed tomography (SPECT/CT)-integrated imaging at 3 hours post- 99m Tc-3PRGD2 injection were performed. The peak time (time to reach peak in dynamic curve), tumor to normal (T/N) ratios, and their change rates relative to pretherapy were calculated. Autoradiography, hematoxylin-eosin (H&E) staining, and CD31 and integrin α v immunohistochemical staining were examined. VX2 tumors were clearly visualized at 3 hours post- 99m Tc-3PRGD2 injection. Tumors in the TG shrank significantly on day 7 after cisplatin administration ( p < .05). The half-life (t 1/2 ) of the radiotracer in heart, liver, and tumor in the NTG were 3.43 ± 0.94 minutes, 13.41 ± 9.17 minutes, and 70.83 ± 33.37 minutes, respectively. The peak time was delayed in the TG immediately and continuously after cisplatin administration compared to the peak time in the NTG. The T/N values and their change rates decreased significantly in the TG compared to the NTG after therapy ( p < .05). The immunostained areas were significantly decreased in the TG ( p < .05) compared to the NTG. 99m Tc-3PRGD2 was an excellent imaging agent for demonstrating tumor angiogenesis. The peak time, T/N values, and their change rates were sensitive parameters to monitor early chemotherapeutic effects. Due to the specific target mechanism and the cost-effective value of 99m Tc-3PRGD2, 99m Tc-3PRGD2 SPECT imaging may have potential in detecting the therapeutic effects of anticancer therapy.